2011
DOI: 10.1002/asna.201012345
|View full text |Cite
|
Sign up to set email alerts
|

On global solar dynamo simulations

Abstract: Global dynamo simulations solving the equations of magnetohydrodynamics (MHD) have been a tool of astrophysicists who try to understand the magnetism of the Sun for several decades now. During recent years many fundamental issues in dynamo theory have been studied in detail by means of local numerical simulations that simplify the problem and allow the study of physical effects in isolation. Global simulations, however, continue to suffer from the age-old problem of too low spatial resolution, leading to much … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 94 publications
0
22
1
Order By: Relevance
“…Due to numerical reasons, the regime of Reynolds, Re and Rm, and magnetic Prandtl, P r m , numbers reached in simulations of magneto-convection and dynamo is different from that of the solar case (see, e.g., Käpylä, 2011). This is so both for the simulations reported here and for those reported previously in the literature (Vögler & Schüssler, 2007;Pietarila Graham et al, 2010;Rempel, 2014;Kitiashvili et al, 2015).…”
Section: Reynolds and Magnetic Prandtl Numbers Of The Simulationscontrasting
confidence: 53%
“…Due to numerical reasons, the regime of Reynolds, Re and Rm, and magnetic Prandtl, P r m , numbers reached in simulations of magneto-convection and dynamo is different from that of the solar case (see, e.g., Käpylä, 2011). This is so both for the simulations reported here and for those reported previously in the literature (Vögler & Schüssler, 2007;Pietarila Graham et al, 2010;Rempel, 2014;Kitiashvili et al, 2015).…”
Section: Reynolds and Magnetic Prandtl Numbers Of The Simulationscontrasting
confidence: 53%
“…Iskakov et al (2007) found supercritical solutions near PrM ≈ 0.1 when using hyperviscosity in their simulations, which does however affect the strength of the spectral bottleneck, as will be discussed in a moment. Even the re-cent convection simulations of Käpylä et al (2018) at a resolution of 1024 3 meshpoints found only decaying magnetic fields at PrM = 0.1.…”
Section: Introductionmentioning
confidence: 94%
“…It is large in the bulk of the solar convection zone, especially if τ is estimated from mixing length theory, which predicts values of Co ranging from 10 −3 near the surface to more than 10 in the deep layers (e.g. Ossendrijver 2003;Brandenburg & Subramanian 2005;Käpylä 2011). This is not captured by present simulations, which might well be due to insufficient density stratification in most numerical simulations so far.…”
Section: Introductionmentioning
confidence: 99%